En hvepserede: læringsstile i e-learning - Lauridsen, Ole (HERMES - Journal of Language and Communication in Business, 2003)
The concept of learning styles is a hornet’s nest. In the last couple of decades, it has gained ground in constructivist learning activities; however, there has been no real con-sensus as to approaches, to definitions, and to integrating it in practice. Besides briefly discussing the must of integrating ICT in HE learning activities, this paper delves into the concept of learning styles and shows how the various subconcepts can be merged in such a way that learning styles become a useful operational concept.